Evolution and Research Opportunities of Digital Forensic Tools: A Bibliometric Analysis - Anggono, Alexander; Prasetyono, Prasetyono; Djasuli, Mohamad; Dwi Syahputri, Rischi (CogITo Smart Journal, 2024)
The use of digital technology has increased rapidly, presenting new challenges such as cybercrime, online fraud and money laundering. To address these threats, digital forensic tools have become crucial in investigating and analyzing electronic evidence to combat increasingly complex digital crimes. Therefore, research and development in the field of digital forensics is crucial to address the growing digital security challenges. This study aims to conduct a bibliometric analysis of digital forensic tools research in the business, management and accounting domains over the past ten years, evaluate the evolution of the research, identify promising research opportunities and provide insights into future directions in the field. Bibliometric analysis was conducted with the help of VOSviewer software on 698 Scopus-indexed articles sourced from ScienceDirect during 2014-2023. Based on the network map analysis, it was found that despite much progress, the field continues to evolve and offers many opportunities for further research and innovation in digital forensic tools related to mobile forensics, memory forensics, anti-forensics, malware analysis, cloud forensics, cybersecurity, machine learning and deep learning, and ethics and privacy in forensic investigations.